Thrombin binding to GPIbα induces platelet aggregation and fibrin clot retraction supported by resting αIIbβ3 interaction with polymerized fibrin - Dubois, Christophe; Steiner, Beat; Kieffer, Nelly; Meyer Reigner, Sylvie C. (Thrombosis and Haemostasis, 2003)
We have investigated the mechanisms leading to platelet aggregation following thrombin interaction with the glycoprotein (GP) Ib-IX-V complex. We show that platelets desensitized for the two thrombin receptors, PAR-1 and PAR-4, are still able to aggregate in response to thrombin and that this aggregation can be inhibited by a monoclonal antibody (VM16d) that blocks thrombin binding to GPIbα, or by pretreatment of platelets with Mocarhagin, a protease that specifically cleaves GPIbα. The thrombin/GPIbα-initiated signaling cascade induces platelet shape change through activation of the Rho kinase p160ROCK, independent of calcium mobilization, transient MEK-1 phosphorylation as well as the cleavage of talin through a calcium-independent mechanism. This signaling cascade does not induce the exposure of high affinity αIIbβ3 integrin receptors, nor does it lead to µ-calpain cleavage of filamin or the integrin cytoplasmic tail. In contrast, we provide evidence that binding of thrombin to GPIbα induces fibrin binding to resting αIIbβ3 leading to fibrin-dependent platelet aggregation and clot retraction, that can be selectively inhibited by αIIbβ3 antagonists such as RGDS, the dodecapeptide or lamifiban, as well as by the fibrin polymerization inhibitor GPRP-amide.
Keywords: Platelets; GPIb-IX-V; thrombin; intracellular signaling; aggregation